Pautas de crianza de padres con hijos en condición de discapacidad (2021)
The main objective of this study was to describe the guidelines for parents developed by parents of children with disabilities, at the Liceo Nacional Almirante Padilla educational institution, in the special, tourist and cultural zone of Riohacha. For its development, the following categories: Parental Guidance and Parental Motivation. It has been supported by authors such as: Manjarrez (2012), García, W. (2012), Muñoz (2012), among others. Regarding the methodology used in the research, which is descriptive with a qualitative approach, the population includes 6 families with children with disabilities from the Liceo Nacional Almirante educational institution Padilla, a semi-structured data collection interview was conducted to include 20 eight (28) questions, which were validated by experts in the field studied. As a result, the results obtained can thus determine that from the beginning parents set standards to ensure the proper functioning of the family, where children have a defined role and although 'they have a disability, they support me in this role and carry out some of the daily activities. you